Childhood extravasation injuries: Improved outcome following the introduction of hospital-wide guidelines. Issue 4 (April 2015) - Ghanem, Ali M.; Mansour, Abdulrab; Exton, Rebecca; Powell, Jonathan; Mashhadi, Syed; Bulstrode, Neil; Smith, Gillian
Summary Introduction Extravasation is an iatrogenic injury that may produce soft tissue necrosis requiring surgical reconstruction (Rose et al., 2008) and (Goon et al., 2006).1, 2 Previous review of extravasation injuries within our hospital showed that early referral to plastic surgeons and washout of high-risk cases lead to favourable outcome in 86% of patients (Gault, 1993).3 Hospital-wide guidelines were introduced in 2005. This paper closes the audit loop by evaluating extravasation injuries outcome following the introduction of these guidelines. Methods All patients referred to the plastic surgery department for extravasation injuries between October 2008 and October 2009 were reviewed. A favourable outcome was defined as resolution without tissue loss requiring surgical reconstruction. Patients were excluded if they sustained the extravasation in other institution. Results A total of 82 extravasation injuries in 78 patients were reviewed during the audit period. Mean age was 3.2 years (Median 0.2 years, Minimum 0 day, and maximum 16.7 years). The injuries were more frequent on the left half of the body (52%) and involving the upper limbs (59%). Mean time to referral was 8 h, with 60% of patients referred within 6 h of the injury, 30% in 6–12 h, and 10% referred after more than 12 h 26% of the injuries required washout treatment - the rest was treated conservatively. Tissue necrosis occurred in 3 cases (4%) but required no surgical intervention due to the small area affected. Conclusion Our audit showed an improved outcome of extravasation injury following introduction of hospital-wide guidelines of early referral to specialist team and washout of high-risk cases.